Aristotle's criticism of Plato's Republic - Mayhew, Robert 1960- (Rowman & Littlefield, 1997)
"The first five chapters of the second book of Aristotle's Politics contain a series of criticisms leveled against Plato's Republic. ... Mayhoew demonstrates that within this criticism Aristotle presents his views on an extremely fundamental issue: the unity of the city and the proper relationship between the individual and the city."--Cover.